PENGGUNAN BAHASA DENTONG PADA SUKU BUGIS DAN MAKASSAR DI KECAMATAN CENRANA KABUPATEN MAROS - Nasrullah, Ince (Jurnal Ilmiah Ecosystem, 2016)
The aim of the research was to observe the use of Dentong Language as minoritylangage of Bugis and Makassar tribes, and acknowladge the status of Dentonglanguage in Bugis and Makassar langage. The populations of the research werespeaker community of Dentong language. Samples were collected with stratifiedsampling method from which the populations were grouped into sub-populationbased on certain criteria of the population. The reshults of the research indicatedthat the use of Dentong and Makassar language tended to be more frequentlyused by speakers of certain ages of adolescents, adults and old. Some reasons whyDentong and Makassar language were used such at the love for anf the fride ofthe languages, so that communication flows smoothly, and references they talkabout were more easily comprehendible.